Antimicrobial susceptibility of staphylococci from bovine milk samples in routine microbiological mastitis analysis in Finland - Taponen, Suvi; Tölli, Heikki-Tapio; Rajala-Schultz, Päivi J. (Frontiers in Veterinary Science, 2023)
The most frequent reason for antimicrobial use in dairy herds is mastitis and knowledge about mastitis-causing pathogens and their antimicrobial susceptibility should guide treatment decisions. The overall objective of this study was to assess antimicrobial resistance (AMR) of staphylococci in mastitic milk samples in Finland. MALDI-ToF MS identified a total of 504 Staphylococcus isolates (260 S. aureus and 244 non-aureus staphylococci, NAS) originating from bovine mastitic milk samples. Phenotypic susceptibility against cefoxitin, ceftiofur, enrofloxacin, gentamycin, oxacillin, penicillin, and tetracycline was evaluated by disc diffusion method and the presence of blaZ, mecA, and mecC genes investigated by PCR. Nitrocefin test assessed these isolates’ beta-lactamase production. The most common NAS species were S. simulans, S. epidermidis, S. chromogenes, and S. haemolyticus. In total, 26.6% of the isolates (18.5% of S. aureus and 35.2% of all NAS) carried the blaZ gene. Penicillin resistance, based on disc diffusion, was lower: 18.8% of all the isolates (9.3% of S. aureus and 28.9% of all NAS) were resistant. Based on the nitrocefin test, 21.5% of the isolates produced beta-lactamase (11.6% of S. aureus and 32.0% of all NAS). Between the Staphylococcus species, the proportion of penicillin-resistant isolates varied, being lowest in S. simulans and highest in S. epidermidis. Resistance to antimicrobials other than penicillin was rare. Of the eight NAS isolates carrying the mecA gene, six were S. epidermidis. One S. aureus isolate carried the mecC gene. Agreement beyond chance, assessed by kappa coefficient, between phenotypic and genotypic resistance tests, was moderate to substantial. Some phenotypically penicillin-susceptible staphylococci carried the blaZ gene but isolates without blaZ or mec genes rarely exhibited resistance, suggesting that the more reliable treatment choice may depend upon genotypic AMR testing. Our results support earlier findings that penicillin resistance is the only significant form of antimicrobial resistance among mastitis-causing staphylococci in Finland.